ANALYSIS CHARACTERS AND CHARACTERIZATIONS IN THE COMIC SANG JAGOAN AS TEACHING MATERIALS IDENTIFYING THE INTRINSIC ELEMENTS OF COMIC FOR CLASS IV STUDENT OF ELEMENTARY SCHOOL - Sholihah, Imroatus; Widjojoko, Widjojoko; Wardana, Deni (Didaktika, 2022)
Now that the alpha generation is more familiar with gadgets than books, there is little hope that children will read books at home. There is great hope for the creation of meaningful learning at school. However, in reality, learning at school is delivered less interestingly, most teachers use the lecture method in delivering material, with the lecture method the learning atmosphere becomes monotonous, causing students to feel bored. In the end, the material presented was not absorbed optimally. The purpose of this research is to describe how the characterizations conveyed by the characters in the story as teaching material identify intrinsic elements for fourth-grade elementary school students. This research uses a qualitative approach with content analysis methods. The research subject in this research is the comic book Serial Akhlak Mulia Sang Jagoan. The data collection technique in this research is a document analysis activity. For data analysis, namely data reduction, data presentation, and drawing conclusions and verification. This research produces teaching materials identifying intrinsic elements and data regarding characters and characterization in the Sang Jagoan comic. There are 2 main characters, 18 subordinate characters and 29 background characters. Through the comic book of Serial Akhlak Mulia Sang Jagoan, the learning atmosphere becomes more interesting, students do not get bored during class and restore students' interest in books.